Indigenous Technology and Agricultural Production: The Case of Poultry Incubator - Ibitoye, Stephen J. (International Journal of Poultry Science, 2011)
Most poultry equipments available in Nigeria are imported and the expensive nature of these equipment, the difficulties encountered in purchasing them, coupled with the problem of lack of fund has made large-scale production of poultry very difficult in Nigeria. This paper therefore, discusses the concept of indigenous technology and the relevance of indigenous technology to the economy of Nigeria. The paper further highlighted the food production problems in the country and finally explained the construction of poultry incubator using indigenous knowledge with the aid of local materials.